Digital Visual Literacy Development via Elementary Self-Care Video Projects - ririn amaliah Putri sarah (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2026)
This study investigates the effectiveness of using educational self-care video production as a learning activity to enhance elementary students’ digital visual literacy while introducing basic concepts relevant to beauty and grooming. Although children increasingly interact with digital media, their ability to critically interpret and create visual content remains limited. To address this gap, a quantitative quasi-experimental one group pretest posttest design was implemented with 60 fifth-grade students from a public elementary school in Padang. Instruments included a digital visual literacy test and a student response questionnaire, both validated by experts with high reliability (α = 0.87 and α = 0.90). The intervention consisted of three sessions focusing on visual literacy introduction, video production workshops, and student presentations. Results demonstrated a substantial improvement in students’ literacy skills, with mean scores increasing from 63.45 to 81.72. A paired-sample t-test indicated a statistically significant difference (t = 14.52, p < 0.001), and Cohen’s d (2.33) showed a very large effect size. Students also reported high motivation, clarity, and confidence through the learning experience.Overall, the findings confirm that integrating self-care video production into elementary learning effectively builds digital visual literacy, supports creativity, and promotes healthy self-care habits aligned with foundational beauty concepts.